Hangnails: Paste them back. Issue 1 (20th October 2019) - Kaur, Ishmeet; Jakhar, Deepak; Misri, Rachita
Abstract: Hangnails are short torn down part of skin surrounding the nails. At times they are very painful. The usual treatment advised is cutting the excess skin with clippers or scissors. To provide an instant relief to the patients, we describe a simpler and effective way to use a surgical glue to paste them back in their original position.